Neuroendorine tumor in the background of adenocarcinoma of midrectum - Mahno, Noor Ezmas; Ong, David; B, Mohd Nurshamizam; Md Nor, Azmi (2015)
Introduction: Synchronous neuroendocrine tumor in the background of midrectal adenocarcinoma is rare. It is a very slow-growing tumor and symptomatic only late in the course of the disease. Case Summary: This is a 60 years old gentleman with no past medical illness presented with persistent loose stool with mucus for 3 months. Colonoscopy found clinically not obstructed upper rectal tumor and biopsy came back as adenocarcinoma. CEA was not raised. CT scan staging showed no distant metastasis and MRI staging reported as T3N0. Intraoperatively, we found midrectal tumor with mucosal ulceration and small liver nodule at segment V. Low anterior resection encompassed of good oncological resection with covering ileostomy was done. Moderately differentiated adenocarcinoma of midrectum with staging of p T2 N0 Mx. Initially, the pathologist reported as the distal doughnut of the specimen was involved. However, after consultation with few experienced pathologist noted an incidental neuroendocrine tumor, grade 1 at the distal doughnut of the specimen with positive immunohistochemical staining for synaptophysin, chromogranin and CD56. Histologically, there were solid nest and occasional rosette of neoplastic cells confined within the submucosal layer, sparing the overlying mucosa. There was no necrosis or muscularis propria invasion. Mitotic figure is low, around 0-1/10 high power field. The Ki67 proliferative index is about 1%. PET scan was arranged to confirm the suspicious liver nodule to rule out metastasis. Serum chromogranin A was pending. He was arranged for oncology review after the PET scan for further plan.